Coronary-Heart-Disease-Associated Genetic Variant at the COL4A1/COL4A2 Locus Affects COL4A1/COL4A2 Expression, Vascular Cell Survival, Atherosclerotic Plaque Stability and Risk of Myocardial Infarction. - Wei Yang; Fu Liang Ng; Kenneth Chan; Xiangyuan Pu; Robin N Poston; Meixia Ren; Weiwei An; Ruoxin Zhang; Jingchun Wu; Shunying Yan; Haiteng Situ; Xinjie He; et al. (PLoS Genetics)
Genome-wide association studies have revealed an association between coronary heart disease (CHD) and genetic variation on chromosome 13q34, with the lead single nucleotide polymorphism rs4773144 residing in the COL4A2 gene in this genomic region. We investigated the functional effects of this genetic variant. Analyses of primary cultures of vascular smooth muscle cells (SMCs) and endothelial cells (ECs) from different individuals showed a difference between rs4773144 genotypes in COL4A2 and COL4A1 expression levels, being lowest in the G/G genotype, intermediate in A/G and highest in A/A. Chromatin immunoprecipitation followed by allelic imbalance assays of primary cultures of SMCs and ECs that were of the A/G genotype revealed that the G allele had lower transcriptional activity than the A allele. Electrophoretic mobility shift assays and luciferase reporter gene assays showed that a short DNA sequence encompassing the rs4773144 site interacted with a nuclear protein, with lower efficiency for the G allele, and that the G allele sequence had lower activity in driving reporter gene expression. Analyses of cultured SMCs from different individuals demonstrated that cells of the G/G genotype had higher apoptosis rates. Immunohistochemical and histological examinations of ex vivo atherosclerotic coronary arteries from different individuals disclosed that atherosclerotic plaques with the G/G genotype had lower collagen IV abundance and thinner fibrous cap, a hallmark of unstable, rupture-prone plaques. A study of a cohort of patients with angiographically documented coronary artery disease showed that patients of the G/G genotype had higher rates of myocardial infarction, a phenotype often caused by plaque rupture. These results indicate that the CHD-related genetic variant at the COL4A2 locus affects COL4A2/COL4A1 expression, SMC survival, and atherosclerotic plaque stability, providing a mechanistic explanation for the association between the genetic variant and CHD risk.